PENGARUH INFUSA KULIT BUAH MANGGIS (Garcinia mangostana) TERHADAP PROFIL FARMAKOKINETIKA PARASETAMOL PADA TIKUS PUTIH JANTAN (Rattus norvegicus L.) - Kesaktian Manurung; Siti Nurbaya; Rezkita Raysyah (Jurnal Farmanesia, 2017)
Mangosteen rind is traditionally used by residents of Southeast Asia, especially Indonesia, to treat various diseases. Drug interactions can reduce or eliminate efficacy and cause serious health problems or problems. This study aims to determine the effect of mangosteen rind infusion on the pharmacokinetic profile of paracetamol administered orally to male white rats. Infusion of mangosteen rind was made in doses of 10% and 20%. The study was conducted by giving the solution successively for 7 days and on the 7th day after 4 hours, paracetamol solution was given orally. Furthermore, the blood of each male rat was taken with a time of 0 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 60 minutes, 90 minutes, 120 minutes, 180 minutes, 240 minutes, 300 minutes, and 360 minutes and measured by UV spectrophotometry. a wavelength of 257 nm. The results showed that there was an effect of mangosteen rind infusion on paracetamol in test animals.